Malaria Prophylaxis During Pregnancy In Primigravidae Using Sulfadoxine/pyrimethamine In Wad Medani-Sudan - Suleiman, Imad Eldin Elgack; Mohamadani, Ahmed A/Alla; Mirgani, Omer Ahmed (Gezira Journal of Health Sciences, 2003)
Objectives:  To evaluate the efficacy of Sulfadoxine/pyrimethamine as a prophylactic    intervention in prevention and control of malaria during pregnancy.                   To compare effect on neonatal low birth weight (LBW) between intervention and control groups.                   To determine the proportion of maternal, neonatal and placental parasitaemia among intervention control groups. Material and methods: A prospective case/control interventional study of 113 primigravidae, 57 as a intervention group and 56 as a control group selected through a cluster sampling technique. After taking their verbal consent, the intervention group received two doses of sulfadoxine/pyrimethamine (SP) in the second and early third trimesters, and followed up according to the WHO antenatal care schedule. The outcomes include the following: Reduction of malaria episodes during pregnancy in primigravidae. Reduction of prevalence of neonatal low birth weight. Determination of the prevalence of maternal, neonatal and placental parasitaemia.